2022
DOI: 10.25130/tjas.19.1.15
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Fragmentation of Plant Densities in The Growth and Yield of Three Varieties of Soybean Glycine max L.

Abstract: The experiment was carried out using three varieties of soybean (Lee74, Taqa and Aeman), cultivated at six plant densities (285714, 200000, 153846, 142857 and 100000 and 76923 plants . ha-1) using the Randomized Complete Block Design in the two regions,( Bany Maqan and Kani panka) belonging to the province of Sulaymaniyah in northern Iraq. The results showed in Bany Maqan , Taqa variety was superior in plant yield and the total yield (19.19 g . plant-1 and 2963.9 kg) respectively, in addition to the num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…The reason may be due to the superiority of the Lee cultivar in this trait due to the nature of the genetic of the cultivars, which was clearly reflected in their response to environmental conditions, and thus increased cell division and elongation, which positively affected the increase in plant height. The result was in line with what was found by some researchers [7,15], who found that soybean cultivars differed among themselves in plant height. Effect of spraying the growth regulator TRIA on plant height directly proportional with increasing the concentration of the growth regulator.…”
Section: Plant Height (Cm)supporting
confidence: 93%
See 1 more Smart Citation
“…The reason may be due to the superiority of the Lee cultivar in this trait due to the nature of the genetic of the cultivars, which was clearly reflected in their response to environmental conditions, and thus increased cell division and elongation, which positively affected the increase in plant height. The result was in line with what was found by some researchers [7,15], who found that soybean cultivars differed among themselves in plant height. Effect of spraying the growth regulator TRIA on plant height directly proportional with increasing the concentration of the growth regulator.…”
Section: Plant Height (Cm)supporting
confidence: 93%
“…Shama cultivar plants needed the least number of days to flowering, with an average of 57.00 days, while Lee cultivar plants needed the more days to reach this stage (60.17 days). This superiority may be due to the different cultivars in their genetic makeup and the extent to which they respond to the surrounding environmental conditions [7,8]. The results also indicated that the number of days decreased when the plants were sprayed with a concentration (60 mg L -1 ) of the TRIA growth regulator until it reached 58.33 days, while the control plants and spraying with the TRIA growth regulator at a concentration of (40 mg L -1 ) recorded the highest number of days to reach flowering amounted to 59.44 days for both.…”
Section: The Number Of Days From Planting To Floweringmentioning
confidence: 99%